Impact of environmental factors on atmospheric radon variations at China Jinping Underground Laboratory - Pei Huang; Wenjie Lv; Rengui Huang; Yangyang Feng; Qibin Luo; Chengtao Yin; Yaxin Yang (Scientific Reports)
Abstract In this study, long-term and continuous monitoring of atmospheric radon concentration, temperature, air pressure, and humidity was conducted at China Jinping Underground Laboratory. The impacts of temperature, humidity, and air pressure on radon concentration in the experimental environment were specifically examined, along with the potential interactions among these factors. Moreover, Radon data were denoised using Singular Spectrum Analysis (SSA) to reveal factors that might influence changes in radon concentration. The possible mechanisms by which these environmental factors influence radon migration have also been explored. This research not only provides new insights into the behavior of radon in underground environments but also offers important references for formulating effective radon management and protective actions.